Study Habits of Student Athletes at the Faculty of Sports Education and Health, Indonesian University of Education - Arrumaisha, Farisha Hasna; Nuryadi, Nuryadi; Juliantine, Tite; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
This article aims to explore the learning habits of student athletes at the Faculty of Sports Education and Health, Universitas Pendidikan Indonesia. Student athletes are faced with challenges in managing time between academic and sports activities, which requires effective and efficient learning strategies. This study identifies learning styles, GPA, learning habits, sports achievements, and the time span to prepare for championships and exams. The sample involved in this study were active students of the Faculty of Sports Education and Health who had participated in official matches at least at the provincial level, as many as 90 people. Based on the results of the analysis, most students at the Faculty of Sports Education and Health have quite high academic accountability and need to be improved.